2nd Selangor geriatrics conference 2023 - Abd Ghafar, Mohd Zaquan Arif (Faculty of Medicine, 2023)
Malaysia officially attained the status of an aging nation in 2022. The healthcare system faced a significant rise in older adult patients across all specialties, compelling healthcare professionals to be more competent in the care of this complex and heterogeneous population. In recognition of this, the UiTM Geriatric Medicine Unit, alongside the Geriatric Medicine Units of Hospital Selayang, Hospital Sg. Buloh and Hospital Tengku Ampuan Rahimah Klang had jointly organized the 2nd Selangor Geriatrics Conference 2023, which was aptly themed 'Practical Dilemmas in Older Adults.' The conference aimed to provide non-geriatricians with an opportunity to listen to the experts discusses common yet complex and vital issues faced by medical professionals when managing geriatric patients.